The interpretation based on transmitted reports (Tafsir bil-Ma’thur): its origin and significance (The International Journal for Scientific Research, 2025)
This study explores Tafsir bil-Ma’thur (narrative-based exegesis): its origin, significance, and impact on shaping interpretive methodologies throughout history. It emphasizes the role of authentic transmission from the Prophet ﷺ, Companions, and Followers in understanding the Qur’an, and outlines the conditions and qualifications required of interpreters to ensure accurate exegesis. The study also highlights its influence on Quranic sciences, preservation of religious identity, and continuity of correct understanding across generations.
Keywords: Origin of Exegesis; Methodology of Exegesis; Quranic Sciences; Interpreter; Religious Identity